If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6 + -4a) + -1(20 + 3a) + -3 = -1(5 + -6a) + (-1a) + 4 (6 * -1 + -4a * -1) + -1(20 + 3a) + -3 = -1(5 + -6a) + (-1a) + 4 (-6 + 4a) + -1(20 + 3a) + -3 = -1(5 + -6a) + (-1a) + 4 -6 + 4a + (20 * -1 + 3a * -1) + -3 = -1(5 + -6a) + (-1a) + 4 -6 + 4a + (-20 + -3a) + -3 = -1(5 + -6a) + (-1a) + 4 Reorder the terms: -6 + -20 + -3 + 4a + -3a = -1(5 + -6a) + (-1a) + 4 Combine like terms: -6 + -20 = -26 -26 + -3 + 4a + -3a = -1(5 + -6a) + (-1a) + 4 Combine like terms: -26 + -3 = -29 -29 + 4a + -3a = -1(5 + -6a) + (-1a) + 4 Combine like terms: 4a + -3a = 1a -29 + 1a = -1(5 + -6a) + (-1a) + 4 -29 + 1a = (5 * -1 + -6a * -1) + (-1a) + 4 -29 + 1a = (-5 + 6a) + (-1a) + 4 Reorder the terms: -29 + 1a = -5 + 4 + 6a + (-1a) Combine like terms: -5 + 4 = -1 -29 + 1a = -1 + 6a + (-1a) Combine like terms: 6a + (-1a) = 5a -29 + 1a = -1 + 5a Solving -29 + 1a = -1 + 5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5a' to each side of the equation. -29 + 1a + -5a = -1 + 5a + -5a Combine like terms: 1a + -5a = -4a -29 + -4a = -1 + 5a + -5a Combine like terms: 5a + -5a = 0 -29 + -4a = -1 + 0 -29 + -4a = -1 Add '29' to each side of the equation. -29 + 29 + -4a = -1 + 29 Combine like terms: -29 + 29 = 0 0 + -4a = -1 + 29 -4a = -1 + 29 Combine like terms: -1 + 29 = 28 -4a = 28 Divide each side by '-4'. a = -7 Simplifying a = -7
| -2-2(w-4)=12 | | 1+126t-t^3=0 | | x^2=24+5x | | -(6-4a)-(20+3a)-3=-5(5-6a)+(-a)+4 | | 31-3y=4 | | (2x-3y)dx-(3x+2y)dx=0 | | (x^2)(7)= | | (3x)(92x)=13/9 | | 23/ | | -15p-5(3-5p)=5(p-4)-40 | | -x/52 | | -10/14 | | x^2-2px+p^2-1=0 | | 4+3x+0x^2+0.5x^3=0 | | 2a^2-15a+12=0 | | 9+18Z-7=9Z+50-7Z | | 2y^2-26y=0 | | -6(x+3)+4x+5=6x+12 | | 4-x^2-2x=35 | | 60-2x=81+x | | 25x^2y^4+10xy^3-15x^2y^5=0 | | 6x^2+15x-7=0 | | f=1/2(hp) | | 7t-16=-51+2t | | 0.75x^2+1.5x-150=0 | | 3-2x^2-8=0 | | 0.3n=-12 | | 4+3x-0.5x^3=0 | | In(e^3)=In(e^3)+In(e^5) | | 8(2q-2)= | | 2(w^2-36)=0 | | 8x+4z=5+7y |